Analisis Numerasi pada Siswa Sekolah Dasar Kelas II - Elya Riza Pahlevi; Arnelia Dwi Yasa; Nyamik Rahayu Sesanti (Lembaga Pengembangan Kinerja Dosen, 2026)
This study was conducted to evaluate the numeracy skills of second-grade students in mathematics lessons involving addition and subtraction of currency. This research is classified as descriptive qualitative. Data collection methods included observation, document collection, and the use of student worksheets. The data analysis employed the Miles and Huberman technique. The data were collected in the form of student worksheets in mathematics lessons in second-grade students at Urek-Urek 2 Elementary School, Malang Regency, with 12 students participating. The analysis revealed three categories of student numeracy ability. These three categories represent numeracy ability groups, divided into low (0-55), medium (55-75), and high (75-100). Based on the results of the second-grade students' numeracy ability evaluation, it can be concluded that the majority of students at Urek-Urek 2 Elementary School have high numeracy ability. The results from the student worksheets indicate that three students are in the low numeracy ability category, two students are in the medium category, and seven students are in the high numeracy ability category. Referring to the questions given, students generally understood the context of the questions, which relate to everyday activities. This demonstrates their ability to think critically to solve problems.